1996
DOI: 10.1104/pp.112.4.1715
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characterization of Root Zn2+ Absorption and Translocation to Shoots in Zn Hyperaccumulator and Nonaccumulator Species of Thlaspi

Abstract: Radiotracer techniques were employed to characterize "Zn2+ influx into the root symplasm and translocation to the shoot i n Thlaspi caerulescens, a Zn hyperaccumulator, and Thlaspi arvense, a nonaccumulator. A protocol was developed that allowed us to quantify unidirectional 65Zn2+ i nflux across the root-cell plasma membrane (20 min of radioactive uptake followed by 15 min of desorption in a 100 p~ ZnCI, + 5 mM CaCI, solution).Concentration-dependent ZnZ+ influx in both Thlaspi species yielded nonsaturating k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
307
1
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(338 citation statements)
references
References 11 publications
26
307
1
2
Order By: Relevance
“…Our results for the three uptake experiments with CaCl 2 desorption resemble previous findings by Lasat et al (1996). The linear nature of Pb uptake by de- sorbed wheat roots suggests that unidirectional Pb influx into the root symplast occurred for at least 120 min (Fig.…”
Section: Short-term Uptake and Long-term Accumulation Of Pb As Affectsupporting
confidence: 88%
“…Our results for the three uptake experiments with CaCl 2 desorption resemble previous findings by Lasat et al (1996). The linear nature of Pb uptake by de- sorbed wheat roots suggests that unidirectional Pb influx into the root symplast occurred for at least 120 min (Fig.…”
Section: Short-term Uptake and Long-term Accumulation Of Pb As Affectsupporting
confidence: 88%
“…Lasat et al [3] have found that hyperaccumulator Thlaspi caerulescens had bigger capacity for Zn 2+ than its relative T. arvense. And such gap is caused by different amounts of Zn transporter proteins [5], which indicates that transporter proteins play a crucial role.…”
Section: Accumulation and Transportmentioning
confidence: 99%
“…Different from other organic pollutants, hazardous heavy metals are indestructible, as they cannot be chemically or biologically degraded. Even worse, some heavy metals can concentrate along the food chain and eventually accumulate in human body because we are at the top of the food chain [1][2][3]. Therefore increasing attention has been paid in recent years to the remediation of polluted soils, among which the use of plants and microbes to remove hazardous metal ions is particularly emphasized [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the maximum capacity for Zn transport across the plasma membrane into the cytosol was 4.5-fold greater in the Znaccumulator T. caerulescens compared with the Znnonaccumulator Thlaspi arvense L. These results indicate that one characteristic of T. caerulescens is a greater capacity for Zn absorption from soil solution into root cells. Enhanced Zn uptake into the root symplasm of T. caerulescens was also associated with a greater capacity for Zn translocation to the shoot (Lasat et al, 1996). For example, after 96 h of exposure to a 65 Zn-labeled uptake solution, 10-fold more 65 Zn accumulated in the shoots of T. caerulescens compared with T. arvense, and 1.2-fold more 65 Zn accumulated in the roots of T. arvense compared with T. caerulescens.…”
mentioning
confidence: 95%
“…In a previous study we reported that Zn influx into root symplasm of Zn-hyperaccumulator and -nonaccumulator species of Thlaspi was mediated by a saturable component with similar affinities for Zn (Lasat et al, 1996). However, the maximum capacity for Zn transport across the plasma membrane into the cytosol was 4.5-fold greater in the Znaccumulator T. caerulescens compared with the Znnonaccumulator Thlaspi arvense L. These results indicate that one characteristic of T. caerulescens is a greater capacity for Zn absorption from soil solution into root cells.…”
mentioning
confidence: 96%